2013
DOI: 10.1021/ma3022019
|View full text |Cite
|
Sign up to set email alerts
|

Polymer/TiO2 Hybrid Nanoparticles with Highly Effective UV-Screening but Eliminated Photocatalytic Activity

Abstract: TiO2 nanoparticle has been considered as a safe sunscreen agent to reduce the skin cancer risk when exposed to sunlight. However, recently it was found that TiO2 particles accelerate the photodamage of skin due to their photocatalytic degradation activity. To effectively eradicate this unwanted effect, we present a new strategy toward the preparation of organic/inorganic hybrid polymer/TiO2 nanoparticles with highly effective UV-screening property but eliminated photocatalytic activity. We prepared new polymer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
49
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(51 citation statements)
references
References 51 publications
(71 reference statements)
2
49
0
Order By: Relevance
“…The unique photo-catalytic activities (PCAs) of TiO 2 nanoparticles [1-4] make them attractive in many potential applications including self-cleaning surfaces [5, 6], antibacterial medical devices [7] and high performance dental composites [8, 9]. Besides their PCAs, TiO 2 NPs are inexpensive and chemically stable; they also have excellent mechanical properties (elastic modulus of TiO 2 is 230 GPa) [1].…”
Section: Introductionmentioning
confidence: 99%
“…The unique photo-catalytic activities (PCAs) of TiO 2 nanoparticles [1-4] make them attractive in many potential applications including self-cleaning surfaces [5, 6], antibacterial medical devices [7] and high performance dental composites [8, 9]. Besides their PCAs, TiO 2 NPs are inexpensive and chemically stable; they also have excellent mechanical properties (elastic modulus of TiO 2 is 230 GPa) [1].…”
Section: Introductionmentioning
confidence: 99%
“…24,25 Recently, many studies have reported the fabrication of hybrid nanocomposites based on a block copolymer acting as template for the incorporation of TiO 2 nanoparticles. 26−34 Most investigations report the in situ method for the synthesis of TiO 2 nanoparticles carried out by means of sol−gel technique inside the block copolymer solution, [27][28][29][30][31]33 while other examples account for the ex situ TiO 2 nanoparticles synthesis prior to incorporation into a block copolymer. 26,32 In our work, semiconductor TiO 2 colloidal nanorods have been obtained ex situ by means of a colloidal chemistry procedure, 35−38 which enabled us to control their size and shape.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The ITO presents appropriate work function value to organic materials, i.e. it has a good ability to collect electrons generated by electron donors, allowing this property to vary according to changes in its active surface [13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%